Results of ARI‐0001 CART19 cell therapy in patients with relapsed/refractory CD19‐positive acute lymphoblastic leukemia with isolated extramedullary disease. Issue 6 (11th March 2022) - Ortiz‐Maldonado, Valentín; Alonso‐Saladrigues, Anna; Español‐Rego, Marta; Martínez‐Cibrián, Nuria; Faura, Anna; Magnano, Laura; Català, Albert; Benítez‐Ribas, Daniel; Giné, Eva; Díaz‐Beyá, Marina; Correa, Juan Gonzalo; Rovira, Montserrat; et al.
Abstract: We evaluated outcomes of 18 patients with isolated extramedullary disease (iEMD) relapsed/refractory (R/R) B‐cell acute lymphoblastic leukemia (B‐ALL) treated with the CD19‐directed CAR T cells ARI‐0001 in two centers (adult and pediatric), including patients treated in the CART19‐BE‐01 trial and the consecutive compassionate use program. iEMD was detected by PET‐CT in 78% (14/18), and/or by cerebrospinal fluid analysis in 28% (5/18). Patients received cyclophosphamide and fludarabine followed by 1 × 10 6 ARI‐0001 cells/kg, initially as a single dose (first patient) and later split into three fractions (10%, 30%, and 60%). Cytokine release syndrome (CRS) occurred in 50% (9/18) of patients, with no cases of grade ≥3 CRS, and 1 case (6%) of grade 1 neurotoxicity. Tocilizumab was used in 6% of patients (1/18). Procedure‐related mortality was 0% at 2 years. Objective responses were seen in 94% (95% confidence interval [CI]: 73%–99%) of patients, with complete responses (CR) seen in 78% (95% CI: 52%–94%) of them. Progression‐free and overall survival were 49% (95% CI: 30%–79%) and 61% (95% CI: 40%–92%) at 2 years. In conclusion, the use of ARI‐0001 cells in patients with R/R ALL and iEMD was associated with a safety and efficacy profile that is comparable with what is observed in patients with marrow involvement and in line with other CART19 products.